Paradoxes of Protection: Compassionate Repression at the Mexico–Guatemala Border. (September 2019) - Galemba, Rebecca; Dingeman, Katie; DeVries, Kaelyn; Servin, Yvette
Executive Summary: Anti-immigrant rhetoric and constricting avenues for asylum in the United States, amid continuing high rates of poverty, environmental crisis, and violence in Guatemala, Honduras, and El Salvador, have led many migrants from these countries to remain in Mexico. Yet despite opportunities for humanitarian relief in Mexico, since the early 2000s the Mexican government, under growing pressure from the United States, has pursued enforcement-first initiatives to stem northward migration from Central America. In July 2014, Mexico introduced the Southern Border Program (SBP) with support from the United States. The SBP dramatically expanded Mexico's immigration enforcement efforts, especially in its southern border states, leading to rising deportations. Far from reducing migration or migrant smuggling, these policies have trapped migrants for longer in Mexico, made them increasingly susceptible to crimes by a wide range of state and nonstate actors, and exacerbated risk along the entire migrant trail. In recognition of rising crimes against migrants and heeding calls from civil society to protect migrant rights, Mexico's 2011 revision to its Migration Law expanded legal avenues for granting humanitarian protection to migrants who are victims of crimes in Mexico, including the provision of a one-year humanitarian visa so that migrants can collaborate with the prosecutor's office in the investigation of crimes committed against them. The new humanitarian visa laws were a significant achievement and represent a victory by civil society keen on protecting migrants as they travel through Mexico. The wider atmosphere of impunity, however, alongside the Mexican government's prioritization of detaining and deporting migrants, facilitates abuses, obscures transparent accounting of crimes, and limits access to justice. In practice, the laws are not achieving their intended outcomes. They also fail to recognize how Mexico's securitized migration policies subject migrants to risk throughout their journeys, including at border checkpoints between Guatemala and Honduras, along critical transit corridors in Guatemala, and on the Guatemalan side of Mexico's southern border. In this article, we examine a novel set of data from migrant shelters — 16 qualitative interviews with migrants and nine with staff and advocates in the Mexico–Guatemala border region, as well as 118 complaints of abuses committed along migrants' journeys — informally filed by migrants at a shelter on the Guatemalan side of the border, and an additional eight complaints filed at a shelter on the Mexican side of the border. We document and analyze the nature, location, and perpetrators of these alleged abuses, using a framework of "compassionate repression" (Fassin 2012) to examine the obstacles that migrants encounter in denouncing abuses and seeking protection. We contend that while humanitarian visas can provide necessary protection for abuses committed in Mexico, they are limited by their temporary nature, by being nested within a migration system that prioritizes migrant removal, and because they recognize only crimes that occur in Mexico. The paradox between humanitarian concerns and repressive migration governance in a context of high impunity shapes institutional and practical obstacles to reporting crimes, receiving visas, and accessing justice. In this context, a variety of actors recognize that they can exploit and profit from migrants' lack of mobility, legal vulnerability, and uncertain access to protection, leading to a commodification of access to humanitarian protection along the route.